Resveratrol Protects Sepsis-Induced Oxidative DNA Damage in Liver and Kidney of Rats - Aydin, Sevtap; Sahin, Tevfik Tolga; Bacanli, Merve; Taner, Gökçe; Basaran, Arif Ahmet; Aydin, Mehtap (Galenos Yayincilik, 2016)
Background: The increases of free radicals have been proposed to be involved in the pathogenesis of sepsis, which leads to multiple-organ dysfunction syndromes. The uses of antioxidants as a complementary tool in the medical care of oxidative stress-related diseases have attracted attention of researchers. Resveratrol (RV) has suggested being antioxidant, anti-proliferative, and anti-inflammatory effects in various experimental models and clinical settings. Aims: This study was undertaken to evaluate the protective effects of RV on oxidative DNA damage induced by sepsis in the liver and kidney tissues of Wistar albino rats. Study Design: Animal experimentation. Methods: Four experimental groups consisting of eight animals for each was created using a total of thirty-two male Wistar albino rats. Sham group was given 0.5 mL of saline intra-peritoneal (ip) only following laparatomy. Sepsis group was given 0.5 mL saline ip only following the induction of sepsis. RV-treated group was given a dose of 100 mg/kg ip RV in 0.5 mL saline following laparatomy. RV-treated sepsis group was given 100 mg/kg ip RV in 0.5 mL saline following the induction of sepsis. A model of sepsis was created by cecal ligation and puncture technique. In the liver and kidney tissues, oxidative stress parameters (malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPX)) and a proinflammatory cytokine (tumor necrosis factor alpha (TNF-alpha)), were evaluated spectrophotometrically and DNA damage was determined by the alkaline single cell gel electrophoresis (comet assay) technique using formamidopyrimidine DNA glycosylase protein. Results: In the RV-treated sepsis group, the levels of MDA and TNF-alpha were lower and GSH levels, SOD and GPX activities were higher than in the septic rats (p<0.05). RV treatment significantly reduced the sepsis-induced oxidative DNA damage in the liver and kidney cells (p<0.05). Conclusion: It is suggested that RV treatment might reduce the sepsis-induced oxidative DNA damages in sepsis-related diseases; however, there is a need for more studies to clear up the protective mechanisms of RV against sepsis.
Keywords: Resveratrol; sepsis; tumor necrosis factor alpha oxidative stress; DNA damage; alkaline single cell gel electrophoresis